Manifestations ORL chez les personnes vivant avec le VIH au CHD/B à Parakou, Bénin - HOUNKPATIN, Spéro; LAWSON ÉPSE AFOUDA, SONIA RUTH JOSÉPHINE; AVAKOUDJO, FRANÇOIS; DOVONOU, COMLAN ALBERT; ATTIKPO, L.; ADJIBABI, WASSI; HOUNKPE, YÉDÉNOU Y. CÉLESTIN (My University, 2012)
.......
Keywords: ORL; VIH; candidoses oropharyngés